Peramalan Hasil Produksi Padi di Kabupaten Solok menggunakan Metode Triple Exponential Smothing Tipe Brown - Kardinal, Ridho; Rizal, Yusmet (Journal of Mathematics UNP, 2023)
Rice is the main food crop which consumes almost the entire population in Solok Regency. The rise and fall of rice production in Solok Regency is caused by the increasingly limited area of rice fields which results in changing the function of paddy fields into settlements or housing. The purpose of this research is to find out the brown type triple exponential smoothing model and to predict rice production in Solok Regency in 2004-2021. Estimates of rice production for the next 5 years show a decline. The forecasting model is:. The result of forecasting rice production for 2004-2021 in tons are 314119,49, 289788,96, 261426,70, 229032,73 and 192607,04.